Aphasia - Menon S (Journal of All India Institute of Speech and Hearing, 1971)
Mr X, 47 years, reported to the clinic on 15-12-69 with a complaint of 'nospeech'. His pretraumatic history was given by his wife. He is a high schoolgraduate, and a forester by vocation. The major interests of his life were huntingand shooting and he was a shikari for many years.